If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 = 11 + -7 Reorder the terms: -7 + 2x = 11 + -7 Combine like terms: 11 + -7 = 4 -7 + 2x = 4 Solving -7 + 2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2x = 4 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 4 + 7 2x = 4 + 7 Combine like terms: 4 + 7 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| 6-2=2+z-2 | | 9(3)-2y=19 | | -5x-7x=x+7 | | y=6sin(4x+7) | | 7x-40=100 | | 20x^2=40x | | -4-5y=21 | | 2(x+1)-5(x+3)=2 | | z^8=-1+i | | 6.25-5X=24 | | 2=-132.4x+6 | | -8x-33=x | | y=-132.4x+6 | | 24x6y3/-6x3y | | cos(2x)+5cos(x)+3=0 | | -4x+3x=-8 | | c=31h+42 | | (14*-7)/5=7 | | 6=2+z | | -7(x-6)+6=48 | | 7p-8q=128 | | 6z-6=7z-5 | | 77*1.8= | | 10-(3n-2)=6-4n | | 3(x-2)=-5x+8 | | 0/-5= | | 13x-y-15=0 | | 4(5x+7)=-23+31 | | 6-4(2f-3)=10 | | ln(x)=ln(x+1)-ln(x-2) | | 6x+5(3/2)=7 | | -3(e-4)=6 |